Effects Of Gender, Educational Background, Job Performance On Job Promotion Study PT Garuda Food Tbk - Aditya Angger Wibowo (Universitas Veteran Bangun Nusantara Sukoharjo, 2024)
The research study was conducted to analyse how much effect gender, educational background, job performance has on employees or employees at PT Garuda Food, Tbk. Researchers took the object of research is PT Garuda Food, Tbk through sampling employees or employees of PT Garuda Food, Tbk. For this type of research is quantitative and descriptive. Sampling for research is 200 respondents sampling through the use of proportional random sampling method. For the method of data analysis through the use of multiple linear regression analysis, partial t test and also f test. The process for calculating through SPSS calculations as well. After testing, it shows that gender, educational background, job performance has a positive and significant effect on job growth